2001
DOI: 10.1002/ana.1283
|View full text |Cite
|
Sign up to set email alerts
|

Small fibers involvement in Friedreich's ataxia

Abstract: Although the involvement of large myelinated sensory fibers in Friedreich's ataxia (FA) is well documented, an impairment of unmyelinated fibers has not been described. We demonstrate an involvement of cutaneous unmyelinated sensory and autonomic nerve fibers in FA patients. We performed a morphological and functional study of cutaneous nerve fibers in 14 FA patients and in a population of control subjects. We used immunohistochemical techniques and confocal microscopy applied to punch skin biopsies from thigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 31 publications
3
48
0
1
Order By: Relevance
“…Response amplitudes (in particular for ABR wave V) were, however, significantly lower, suggesting reduced neural populations in the auditory brainstem. This finding is consistent with reports of axonal degeneration in other sensory systems for individuals with FRDA [Hughes et al, 1968;Nolano et al, 2001].…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Response amplitudes (in particular for ABR wave V) were, however, significantly lower, suggesting reduced neural populations in the auditory brainstem. This finding is consistent with reports of axonal degeneration in other sensory systems for individuals with FRDA [Hughes et al, 1968;Nolano et al, 2001].…”
supporting
confidence: 83%
“…Desynchronization may occur through demyelination of the auditory nerve [Waxman, 1977] or disrupted synaptic transmission between cochlear inner hair cells and the auditory nerve [Glowatzki and Fuchs, 2002]. In listeners with FRDA, auditory pathway disruption is likely due to axonal degeneration [Hughes et al, 1968;Nolano et al, 2001] rather than desynchronization (hence, the reduced ABR amplitudes -but normal response latencies -observed in our subjects who still had an ABR at the time of testing). Zeng et al [2005] have, however, suggested that the response from a reduced number of neural elements to a subtle timing cue could be difficult to detect because of its similarity to background spontaneous activity.…”
Section: Discussionmentioning
confidence: 92%
“…4 More recently, reduced MC density, distorted MC structure, focal thinning or loss of myelin, and short myelin internodes coupled with decreased sensitivity to touch have been reported. [5][6][7] Functional studies of touch conveyed by cutaneous mechanoreceptors in glabrous skin found that detection of small raised dots (bumps) on a smooth surface using the finger pad was signaled by MCs. 8,9 Based on these studies, we devised a simple device called the Bumps to quantify tactile sensitivity on the finger pads.…”
Section: Discussionmentioning
confidence: 99%
“…24 However, some of our findings (warm threshold abnormalities and ENF loss) also suggest an involvement of C fibers in CMT1A, although we cannot have morphologic evidence, since it is not possible to distinguish between C and A-d fibers, whose cutaneous terminal branches are both unmyelinated. 25,26 The involvement of small fibers in conditions affecting mainly large fibers has been previously reported, [27][28][29] implying that congenital or acquired mechanisms underlying the degeneration of large fibers may also affect small fibers. In CMT1A, abnormalities of the interaction between axon and Schwann cells may play a causative role in the distal degeneration of unmyelinated fibers, since PMP22 is also present in the plasma membrane of nonmyelinating Schwann cells.…”
Section: Statistical Analysis We Used Student T Test For Unpaired Datamentioning
confidence: 94%